DNA Mini-Barcoding: A Derived Barcoding Method for Herbal Molecular Identification - Gao, Zitong; Liu, Yang; Wang, Xiaoyue; Wei, Xuemin; Han, Jianping (Frontiers in Plant Science, 2019)
In recent years, the demand for natural herbal products (NHP) has increased; however, the quality of these products is difficult to confirm due to the lack of a comprehensive quality control system. Traditional methods are not effective in detecting processed ingredients. DNA barcoding is an established technique that has been used for more than 10 years. This technique uses short standard sequences (generally 200–600 bp) to identify species. While a complete DNA barcode is difficult to obtain from NHP due to DNA degradation, mini-barcoding is a complementary tool to identify species in NHP. DNA mini-barcoding uses smaller DNA segments for polymerase chain reaction amplification and can be applied to identify species rapidly. The present review summarizes the development and application of DNA mini-barcodes over recent years and discusses the limitations of this technique. This review also compares mini-barcoding and meta-barcoding, a technique using universal polymerase chain reaction primers to simultaneously amplify multiple DNA barcodes and identify many species in a single environmental sample. Additionally, other detection methods that can be combined with mini-barcodes, such as nucleotide signatures, high-resolution DNA melting analysis, and gold nanoparticles, are discussed. DNA mini-barcoding can fill the gaps left by other methods in the field of herbal molecular identification.